Harmonic Power Distribution and Harmonic Compensation in the Standalone Microgrid with Nonlinear Loads - JIA Yaoqin; ZHAO Yongfei; HU Changhua (Kongzhi Yu Xinxi Jishu)
In the utilization of renewable energy resource, microgrid can expand the range of application for distribution generation. However, the key issue of microgrid is how to keep the stability of voltage and frequency and obtain proper load sharing between distributed generation units. First, the droop control strategy of distributed generation power in parallel was analyzed in detail. In the case of connecting nonlinear load, the influence was also analyzed. The droop control based on harmonic power-conductance and the control method of suppressing the voltage distortion via harmonic compensation were proposed. The simulation and experiment results verified the effectiveness of this control method.